Case report: Laparoscopic treatment of gastro-omental hemangioma with hemorrhage: two cases reports and review of literature - Yin, Long-Kuan; Liu, Jian-Jun; Feng, Yi-Guo; Yuan, Hua-Yan; Wang, Wei; Bai, Xiang-Yu; Wang, Pan (Frontiers in Surgery, 2023)
Background Spontaneous hemorrhage of gastro-omental hemangioma is a rare disease. The treatment strategy for this disease changes as it develops. In the acute stage, surgery is the first priority, among which laparoscopic treatment should be the most frequently considered option in large general hospitals. Due to the rarity of this disease, such cases have rarely been reported. Case description We present the first report of two eldely cases with gastro-omental hemangioma with hemorrhage by laparoscopic treatment. Both cases were initially admitted with upper abdominal pain, and abdominal computed tomography (CT) scan revealed masses alongside the greater curvature of the stomach. Laparoscopic surgery was conducted immediately in both patients. The two cases recovered well after surgery, and no obvious abnormalities were observed in the follow-up period. Conclusion Gastro-omental hemangioma rupture remains an uncommon cause of intraperitoneal hemorrhage. Timely diagnosis and surgery are paramount for treatment. Medical institutions with the correct technology and equipment should perform laparoscopic treatment to minimize surgical trauma and promote rapid recovery of patients with abdominal apoplexy.